MODEL OF TAKEOFF AND LANDING OPERATIONS FOR CALCULATING OF AERODROME capacity - I. Yu. Agafonova; L. E. Rudelson; A. I. Stepanova (Научный вестник МГТУ ГА, 2016)
The procedures for takeoff and landing of aircraft flow are discussed. An approach to the construction of a model for calculation of aerodrome capacity is proposed. Decomposition of model is conducted and one of its elements - the approach mode is investigated. The estimation of the time interval for this mode and limitations on the minimum distances between aircraft in the stream are shown.